Pengaruh Regulasi Diri Dan Efikasi Diri Terhadap Hasil Belajar Matematika Siswa - Evi Febriani (Cahaya Ilmu Bangsa Institute, 2023)
This study aims to know direct positive effects of self-regulation and self-efficacy towards mathematics learning outcomes, and indirect positive effects of self-regulation and self-efficacy towards mathematics learning outcomes. The population of this study are students grade 10th-12th in Senior High School Tarbiyatun Nasyiin. The sampling technique in this study was cluster random sampling, so the sample is 122 students from Senior High School Tarbiyatun Nasyiin Grujugan Larangan. The data was collected using questionnaire and test, then analyzed using descriptive statistics and path analysis. The results of the study show that self-regulation and self-efficacy of students are in the medium category, while students' mathematics learning outcomes are still relatively low. The low of creative thinking abilities are approved by self-regulation and self-efficacy.